DETERMINAN TINGKAT SOLVABILITAS PADA PERUSAHAAN ASURANSI JIWA SYARIAH PERIODE 2014-2018 - Evrilyan, Herlin; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study is to analyze the factors that influence the solvency of the performance of Islamic life insurance companies in the 2014-2018 period. This research uses a quantitative approach with panel data regression analysis method. The data used in this study are secondary data, using a purposive sampling method. The data used by researchers is the financial statements of Islamic life insurance companies in the 2014-2018 period. The population in this journal is the Islamic life insurance industry of 24 companies, while the sample in this journal is 10 samples of Islamic life insurance companies registered with the Financial Services Authority. Partially the findings of this study, which are applied through the variable Company Size and Liquidity Ratios have a significant effect on Solvency, while Claim Expense Ratio, Underwriting Ratio, and Management Cost Ratio have no significant effect on Solvency. Simultaneously Company Size, Liquidity Ratio, Claim Cost Ratio, Underwriting Ratio, and Management Cost Ratio have a significant effect on solvency with a significant level of 0,000 0.05. With the Adjusted R2 value, the result is 0.715554, which means 71.49%, while the remaining 28.51% is influenced by other variables outside this study.Keyword: Islamic Life Insurance, solvency, Risk Based Capital, Islamic Insurance